The Guidelines for Strengthening High Performance Organization in Secondary School in Phitsanulok - Lakthan, Rujipat; Pooncharoen, Nattachet (Journal of Graduate MCU KhonKaen Campus, 2024)
The objectives of this research were to study needs and the guidelines for strengthening high performance organizations in secondary school in Phitsanulok. There were two steps of the research, the first step was the study of the needs for strengthening high performance organizations in secondary school in Phitsanulok.The sample were 306 government teacher in Phitsanulok-Uttaradit Secondary Educational Service Area Office. The target were 39 government teacher in administrative positions. The tools used in the study were dual–response format questionnaires. The Data was collected by the researcher itself. The data analysis was processed by statistical analysis which are percentage mean and standard deviation (S.D.) while the Priority Needs Index ( ) and the content analysis was performed to assess the needs. The second step was the study of guidelines for strengthening high performance organizations in secondary school in Phitsanulok. The data was collected by using interviewing method which was held by the 3 qualified experts. The data were analyzed by content analysis. The results were shown that: 1. The overall needs assessment index for strengthening high performance organizations in secondary school in Phitsanulok was equal to 0.108. The process and resource organization were the highest needs assessment indexes ( = 0.142), followed by the organizational learning ( = 0.111), while the personnel development was the lowest ( = 0.089. 2. The study of strengthening high performance organizations in secondary school in Phitsanulok found that school must organize to obtain information from all parties. Bring it to a meeting to plan operations within school. Set a vision and strategies for managing school that are based on principles and theories of educational administration. Administrators must supervise Follow up on operations within the school to achieve success according to the set target values. Allocate resources to each department as appropriate to the school context. Encourage personnel to develop themselves, there is always learning of up-to-date knowledge. Promote the exchange of knowledge in the professional learning community (PLC), develop teachers with potential and have the spirit of being a teacher to become a high-performance organization.